Effect of substrate mineralogy, biofilm and extracellular polymeric substances on bacterially induced carbonate mineralisation investigated with in situ nanoscale ToF-SIMS - Anant Aishwarya Dubey; Pelina Toprak; Allan Pring; Carlos Rodriguez-Navarro; Abhijit Mukherjee; Navdeep K. Dhami (Scientific Reports)
Abstract Bacterial mineralisation of calcium carbonates (CaCO3) has become a focal point of interest in the scientific community owing to their versatile applications as biomaterials. However, despite extensive research, the knowledge on factors influencing biogenic CaCO3 polymorph (calcite, vaterite or aragonite) selection in nature remains obscure. Bacterial mineralisation happens in nature on diverse substrates by different pathways, often in the presence of organic matter such as biofilm and extracellular polymeric substances (EPS) secreted with the regular metabolic activities of microbes. This study examines the bacterial CaCO3 mineralisation process by two distinct pathways on different natural substrates with advanced analytical techniques, including Time of Flight- Secondary Ions Mass Spectrometry (ToF-SIMS). A high EPS-producing microbe (Bacillus subtilis, BS) was compared with the standard ureolytic strain (Sporosarcina pasteurii, SP). Natural geological minerals, including apatite, calcite and quartz, were selected as substrates. This study demonstrates that SP favours the precipitation of rhombohedral calcite crystals (2 to 40 μm in size), regardless of the mineral substrate. In contrast, the EPS-producing BS culture induced the formation of significantly larger vaterite structures (20 to 100 μm in size) in spheroid and hexagonal shapes. The mineralogy of precipitates was confirmed with Raman spectroscopy. ToF-SIMS enabled the spatial tracking of organic macromolecules and the adsorption of calcium ions on them. The functional groups of the EPS involved in these interactions were characterised by Fourier Transform Infrared Spectroscopy (FTIR). This study reveals that microbial activity dominates over substrate mineralogy in selecting the phase and shaping the morphology of biogenic CaCO3, with EPS playing a crucial role in promoting the aggregation of small nanocrystals into large vaterite structures and their stabilisation.